From Pockets to Pupils: Unraveling the Impact of Ethnicity and Family Income on Household Financing in Basic Education - Khanal, Basudeb (Journal of Research and Development, 2024)
This study examines the role of ethnicity and household income on household financing of basic education in Nepal. A survey was conducted among 380 households with children pursuing basic education. Employing a descriptive and correlational research design, binary logistic regression was applied to analyze the data. The findings disclose that both ethnicity and household income significantly affect household financing of basic education. This study adds valuable insights to our comprehension of the socio-economic dynamics that impact the financing of basic education within Nepal. By shedding light on the impacts of ethnicity and household income on education financing, it deepens our thought of the complex interplay between socioeconomic factors and educational access. Thus, this research contributes to a more comprehensive understanding of the socio-economic landscape of education financing in basic education in Nepal, providing a foundation for informed policymaking and targeted interventions designed to foster greater equity and accessibility in basic education.